Modulation of charge transport properties in poly(3, 4-ethylenedioxythiophene) nanocomposites for thermoelectric applications. (21st December 2017) - Galliani, Daniela; Battiston, Simone; Ruffo, Riccardo; Trabattoni, Silvia; Narducci, Dario
Abstract: Conjugated polymer poly(3, 4-dioxyethylenthiofene) (PEDOT) has recently gained attention for room-temperature thermoelectric applications due to its low cost, safety and the possibility of easy processing. This makes it an interesting prospective alternative to tellurides commonly used around room temperature. Still, low thermoelectric efficiencies of polymers might be more easily increased, were a model of its transport properties available. The aim of this paper is to validate a model recently reported, making use of the concept of transport energy to frame the onset of transport properties reported over the last few years in the literature. To this aim, PEDOT and PEDOT-based nanocomposites embedding CuO nanoplatelets were prepared and analysed. We found that the model adequately fits the trends observed in pure PEDOT and in its nanocomposites. Transport and Fermi energy were verified to depend on the polymer oxidation level only, while the transport coefficient was found to be sensitive to PEDOT stacking and was modulated by the introduction of CuO nanoplatelets.